Effect of pretreatment strategies on halophyte Atriplex crassifolia to improve saccharification using thermostable cellulases - Nawaz, Ali; Qadoos, Khadija; Haq, Ikram Ul; Feng, Yiwei; Mukhtar, Hamid; Huang, Rong; Jiang, Kankan (Frontiers in Bioengineering and Biotechnology, 2023)
Bioethanol is believed to be an influential revolutionary gift of biotechnology, owing to its elevating global demand and massive production. Pakistan is home to a rich diversity of halophytic flora, convertible into bounteous volumes of bioethanol. On the other hand, the accessibility to the cellulosic part of biomass is a major bottleneck in the successful application of biorefinery processes. Thus, pre-treatment of lignocellulosic biomass is a basic prerequisite for its effective enzymatic hydrolysis. The current research was aimed at exploring the best pre-treatment method for the bioconversion of halophyte Atriplex crassifolia into saccharides using three thermostable cellulases. Atriplex crassifolia was subjected to acid, alkali and microwave pre-treatments, followed by compositional analysis of the pre-treated substrates. Maximum delignification i.e. 56.6% was observed in the substrate pre-treated using 3% HCl. Enzymatic saccharification using thermostable cellulases also validated the results where the highest saccharification yield i.e. 39.5% was observed for the sample pre-treated using same. Maximum enzymatic hydrolysis of 52.7% was obtained for 0.40g of the pre-treated halophyte Atriplex crassifolia where Endo-1,4-β-glucanase (300U), Exo-1,4-β-glucanase (400U) and β-1,4-glucosidase (1000U) were simultaneously added and incubated for 6 h at 75ºC. The reducing sugar slurry obtained after optimization of saccharification was utilized as glucose in submerged fermentation for bioethanol production. The fermentation medium was inoculated with Saccharomyces cerevisiae, incubated at 30ºC and 180 rpm for 96 hours. Ethanol production was estimated using potassium dichromate method. Maximum production of bioethanol i.e. 16.33% was noted at 72 h. It can be concluded from the study that Atriplex crassifolia owing to its high cellulosic content after pre-treatment using dilute acid method, yields a substantial amount of reducing sugars and high saccharification rates when subjected to enzymatic hydrolysis using thermostable cellulases, under optimized reaction conditions. Hence, the halophyte Atriplex crassifolia is a beneficial substrate that can be utilized to extract fermentable saccharides for bioethanol production.